Studi Netnografi tentang Respon Masyarakat Daring terhadap Keputusan Perpanjangan Kontrak Shin Tae Yong sampai Tahun 2027: Indonesia - Praditya, Alvin; Rahmadi, M. Firdaus; Soraya, Nadia Nur (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The decision of PSSI to extend Shin Tae Yong's contract until 2027 has become a hot issue that sparked widespread discussion on social media, with public opinion divided between support for his achievements and criticism of the less-than-optimal results. Using a netnographic approach, this study explores the dynamics of online public perception regarding the decision and how social media shapes and reflects public opinion within the context of sports management. The purpose of this study is to understand the online community’s response to the extension of Shin Tae Yong’s contract until 2027. The method used in this research is a netnographic approach. Data were collected from publicly available information where everyone is free to share anything through social media. The data collection techniques used were documentation and field notes. The results indicate that the online community’s responses to the contract extension decision are largely positive, featuring unique comments, irrelevant comments to the posts, as well as suggestions and advice directed at Shin Tae Yong and the PSSI leadership. Some comments expressed disagreement, and there were also sarcastic remarks aimed at the commentator Tommy Welly.